(untitled) (Indian Journal of Nematology, 2024)
Severe infestation by root-knot nematode was observed with wilting and dying of guava (Psidium guajava L.) plants intercropped in coconut garden at Kayamkulam, Kerala, India in 2020. The nematode was isolated from infected guava roots and subjected to morphological and molecular characterizations. The morphological identity was confirmed by typical morphological and morphometric features of second-stage juveniles as well as the characteristic perineal pattern of adult females. Sequencing of 28S ribosomal RNA gene using D2a and D3b primers as well as cytochrome c-oxidase subunit-1 (COI) gene showed more than 99 per cent identity with Meloidogyne enterolobii. Molecular identity was further confirmed with M. enterolobii-specific SCAR markers (MeF and MeR), which yielded a positive amplification of nucleotide having approximately 236 bp size band in the agarose gel. The occurrence of M. enterolobii also from a guava seedling collected from a private nursery located about 40 km from Kayamkulam warrants strict quarantine measures to halt the further spread of this exotic nematode into new areas. This is a new record of M. enterolobii from Kerala, India, and a biosecurity risk associated with other crops in the region.